Bashkir Wörgl: Succesfsful Farm Rescue. Implementing Gesell Money in the Shaimurat Farm, Russia - Ljovkin, Vladim E.; Ljovkina, Anastasia O. (PARTECIPAZIONE E CONFLITTO, 2020)
Gesell’s money has been successfully used in different territories during social-economic crises to boost business growth and to improve the welfare of the territory. However, this money has remained an exotic, rarely used tool. This situation makes it particularly important to analyze every case of using this complementary currency in different contexts. The purpose of this article was to describe a new case of using Gesell money in Shaymuratovo agricultural enterprise (Karmaskalinsky district, Bashkiria, Russia) and analyze it through the comparison of its social-economic effects with the results of the most famous case of using Gesell’s money - Wörgl case. We revealed common positive social-economic effects of using the complementary currency: maintaining employment and creating new jobs, increasing turnover, stimulating business activities, developing infrastructure, paying off debts and improving the social-economic at-mosphere. We concluded that historical, geographical, political and other circumstances of implementing Gesell’s money may determine its viability, specific form, rules of its functioning, and quantitative results. Nevertheless, implementing Gesell money has common types and qualitative characteristics of anti-crisis social-economic effects.